1970
DOI: 10.4314/sajas.v46i3.13
|View full text |Cite
|
Sign up to set email alerts
|

Pomegranate seed oil rich in conjugated linolenic acids reduces in vitro methane production

Abstract: The objective of this study was to determine the effect of pomegranate (Punica granatum L.) seed oil (PSO) on gas and methane (CH4) production, ruminal fermentation and microbial populations under in vitro conditions. Three treatments consisting of a control diet containing 10 mg tallow (CON); the control diet with 5 mg PSO + 5 mg tallow (MPSO) and the control diet containing 10 mg PSO (HPSO) were compared. Ten mg of the experimental fat/oil samples were inserted into a gas-tight 100 mL plastic syringe contain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 1 publication
0
5
1
Order By: Relevance
“…In contrast to our experiment, the addition of 6 % olive, sunflower or linseed oil to high concentrate diets did not significantly affect the number of ciliate protozoa (Vargas et al, 2020). Pomegranate oil increased the number of protozoa under in vitro conditions (Maleki et al, 2016). Pomegranate oil is a rich source of punicic acid, which is an isomer of linolenic acid.…”
Section: In Vitro Fermentationcontrasting
confidence: 94%
See 1 more Smart Citation
“…In contrast to our experiment, the addition of 6 % olive, sunflower or linseed oil to high concentrate diets did not significantly affect the number of ciliate protozoa (Vargas et al, 2020). Pomegranate oil increased the number of protozoa under in vitro conditions (Maleki et al, 2016). Pomegranate oil is a rich source of punicic acid, which is an isomer of linolenic acid.…”
Section: In Vitro Fermentationcontrasting
confidence: 94%
“…On the other hand, addition of 5 or 10 mg pomegranate oil to alfalfa hay and concentrate reduced total in vitro gas production (Maleki et al, 2016), and oleic acid (35 and 70 g kg −1 of substrate dry matter) decreased in vitro gas production in the diet containing rye and cornmeal (Zhang et al, 2008). This decrease could be associated with the suppression of density and activity of rumen bacteria by dietary UFA supplementation, particularly the cellulose-utilizing bacteria (Palmquist and Jenkins, 1980).…”
Section: In Vitro Gas Productionmentioning
confidence: 97%
“…(2021) and Maleki et al. (2016), who reported that pomegranate by‐products might be an option for methane‐mitigating feed supplements, which might be beneficial to nutrient utilization and growth in ruminants.…”
Section: Discussionmentioning
confidence: 99%
“…Abarghuei et al (2014) and Rajabi et al (2017) suggested that PPE supplementation has reduced total protozoa enumeration. Maleki et al (2016) indicated that total bacteria and protozoa counts increased with rising PSO levels, whereas the methanogen population declined significantly.…”
Section: Factormentioning
confidence: 99%
“…Similarly, a report has proven that the concentration of total VFA and molar proportion of individual VFAs were not affected by the inclusion of Pomegranate Peel Extract in the diet(Abarghuei et al, 2013).Due to adding a pomegranate by-product, Jami et al (2012) observed an increase in abundance in Lactic acid bacteria and methanogen archaea community, moreover a decrease in abundance in main cellulolytic bacterial species Abarghuei et al, (2014). andRajabi et al, (2017) suggested that PPE supplementation has reduced total protozoa enumeration Maleki et al, (2016). indicated that total bacteria and protozoa counts increased with rising PSO levels, while the methanogens population declined signi cantly.…”
mentioning
confidence: 94%